Mimetic politics: dyadic patterns in global politics - Farneti, Roberto (Studies in Violence, Mimesis, & Culture, 2015)
Intro -- Contents -- Introduction -- Chapter 1. A New (Mimetic) Paradigm for Our Postsacrificial Times -- Chapter 2. The Mimetic Context of the "New Wars" -- Chapter 3. Cleavage Lines in Global Politics -- Chapter 4. A Mimetic Perspective on Conflict Resolution -- Chapter 5. A Political Theology of the Empty Tomb -- Epilogue. A Genealogy of "Planetary Reciprocity" -- Notes -- References -- Index.